TNF-α downregulates the peroxisome proliferator activated receptor-α and the mRNAs encoding peroxisomal proteins in rat liver - Beier, Konstantin; Völkl, Alfred; Fahimi, H. Dariush (FEBS letters, 1997)
We have studied the effects of TNF-α on the mRNAs coding for the peroxisome proliferator activated receptor α (PPAR-α), and for catalase (Cat), acyl-CoA oxidase (AOX), multifunctional enzyme (PH), and β-actin in rat liver. Total RNA was isolated from livers of male SD-rats 16 h after administration of a single dose of 25 μg TNF-α and mRNAs were analyzed by a novel dot blot RNase protection assay. The mRNAs for PPAR-α and for Cat, AOX and PH were significantly reduced by TNF-treatment. In addition, the level of PPAR-α protein was also decreased after TNF. In contrast, the mRNA for β-actin was markedly increased implying that the effect of TNF on PPAR-α and the peroxisomal mRNAs is highly selective. This effect may have important implications in perturbation of the lipid metabolism induced by TNF-α.
Im Titel ist "alpha" als griechischer Buchstabe dargestellt
Gesehen am 25.03.2024